2017
DOI: 10.1155/2017/5238134
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Enterocyte in Intrauterine Growth Retarded Pig Neonates

Abstract: The intestine of intrauterine growth retarded (IUGR) neonates showed different morphology compared to neonates born with normal body weight (NBW). The aim of the present study was to investigate the ultrastructure and proteomic profile of the gut epithelium in IUGR pig neonates with special attention to the digestive and absorptive function. Intestine tissue samples were investigated in 7-day-old IUGR and NBW littermate piglets using histometry, immunofluorescence, scanning electron microscopy (SEM), and mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…With the use of confocal microscope, it was demonstrated that the expression of lamin A/C was reduced over the entire length of the mucous membrane. The reduced expression of this protein can be the cause or the consequence of the slowed-down mitotic divisions in the intestines of the IUGR piglets (Ferenc et al, 2017). Significant differences were also found in the architecture of the cytoskeleton not only in the foetal enterocytes but also in enterocytes of adults.…”
Section: Consequences Of the Thrifty Phenotype -Peculiarities In The mentioning
confidence: 97%
See 3 more Smart Citations
“…With the use of confocal microscope, it was demonstrated that the expression of lamin A/C was reduced over the entire length of the mucous membrane. The reduced expression of this protein can be the cause or the consequence of the slowed-down mitotic divisions in the intestines of the IUGR piglets (Ferenc et al, 2017). Significant differences were also found in the architecture of the cytoskeleton not only in the foetal enterocytes but also in enterocytes of adults.…”
Section: Consequences Of the Thrifty Phenotype -Peculiarities In The mentioning
confidence: 97%
“…The more intense is the absorption of macromolecules, the larger are the vacuoles. An exception to this are foetal enterocytes in piglets with intrauterine growth retardation (IUGR) syndrome in which the fusion of smaller vesicles into giant vacuoles was halted (Mickiewicz et al, 2012;Ferenc et al, 2017;Figure 3).…”
Section: Why and How Foetal-type Enterocytes Can Absorb Macromolecules?mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the pig provides an adequate animal model to investigate the implications of IUGR, as it shows similarities with humans regarding anatomy, metabolism and rapid postnatal growth rate (Ferenc et al 2017).…”
Section: Introductionmentioning
confidence: 99%